A nanocrystalline soft magnetic alloy and its preparation method and application
By adjusting the element ratio of nanocrystalline soft magnetic alloy and the two-step heat treatment process, the problems of unstable performance and high cost of nanocrystalline soft magnetic alloy in AC and DC signal processing are solved, and high performance and high stability AC and DC are achieved Performance, suitable for mass production of A type residual current transformers.
Patent Information
- Application Number
- CN202410262224.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-07
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-03-07
AI Technical Summary
The existing nanocrystalline soft magnetic alloys have unstable performance when processing AC and DC signals, and there are problems of large performance fluctuations and high cost during mass production, especially in the application of A-type residual current transformers, which is difficult to take into account both magnetic and mechanical properties.
By adjusting the proportion of components of nanocrystalline soft magnetic alloys, including Si, B, Cu, Nb, Ce, P, Zr, Co and Fe, a two-step heat treatment process is used to control the grain size and magnetic domain structure to avoid element doping Too many adverse effects on performance and improve AC and DC performance.
It realizes high performance and high stability of nanocrystalline soft magnetic alloys in AC and DC signal processing, reduces performance fluctuations, is suitable for mass production of A-type residual current transformers, and has reasonable cost control.
Smart Images

Figure CN118053644B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soft magnetic materials and relates to a soft magnetic alloy, in particular to a nanocrystalline soft magnetic alloy and a preparation method and application thereof. Background Art
[0002] Residual Current Device (RCD) is widely used in the field of low-voltage electrical appliances to detect the size of residual current and prevent safety accidents by timely cutting off the power supply. However, the AC type residual current protectors currently in widespread use are mainly designed for residual current of industrial frequency sinusoidal AC. As the application scenarios continue to expand, when industrial or daily electrical equipment fails, the residual current generated is no longer just a simple sinusoidal power frequency signal. The pulsating DC component will cause the induced magnetic field of the residual current transformer (RCT) to be biased or even saturated, causing the residual current protector to refuse to operate, resulting in serious safety accidents. Therefore, the A-type residual current transformer, which can protect both sinusoidal AC and pulsating DC residual currents, came into being.
[0003] Finemet is a nanocrystalline soft magnetic material with high-value application prospects. It has excellent soft magnetic and mechanical properties and is widely used in the preparation of residual current transformer cores. At present, the application of Finemet in the field of type A residual current transformers still has the following problems: excessive pursuit of local high performance, monotonous evaluation system, and because the core of type A residual current transformer does not pursue extreme performance in a specific working section, it causes excess performance; the preparation of type A residual current transformers often requires magnetic field annealing treatment, and magnetic materials are easily deformed or even displaced when subjected to magnetic field forces, resulting in excessive performance fluctuations when applied in batches.
[0004] CN108559926A discloses a method for preparing an iron-based amorphous strip and a high-frequency and high-permeability nanocrystalline alloy. The iron-based amorphous strip comprises the following components in molar parts: 67-74.2 parts of Fe, 16-19.2 parts of Si, 6.5-8.5 parts of B, 2-3 parts of Nb, 0.2-1 parts of V, 1-1.3 parts of Cu and 0.1-2.2 parts of Co. V and Co are used to partially replace Nb, thereby reducing the cost of raw materials, and the production process does not need to be combined with transverse magnetism. Compared with traditional nanocrystalline alloys, the magnetic permeability of this type of material decreases, the coercive force increases, and the required heat treatment time is longer, which is not conducive to large-scale batch production. The material is suitable for occasions that pursue high magnetic permeability and high-frequency performance, but there is a problem of excess performance when used in the low-frequency field.
[0005] CN109706290A discloses a magnetic field heat treatment method for nanocrystalline magnetic cores suitable for type A leakage, comprising the following steps: (1) placing the nanocrystalline magnetic core to be treated in a transverse magnetic furnace and introducing protective gas; (2) performing heat treatment and magnetic treatment, including: a first stage: raising the temperature from room temperature to about 560°C, heating and keeping warm for about 90 minutes; a second stage: cooling the nanocrystalline magnetic cores after the first stage heat treatment to room temperature; a third stage: placing the nanocrystalline magnetic cores cooled in the second stage in a transverse magnetic furnace, raising the temperature from room temperature to about 420°C, heating and keeping warm for about 60 minutes, and performing transverse magnetic treatment while annealing; a fourth stage: removing the nanocrystalline magnetic cores from the furnace and cooling them to room temperature; and (3) collecting the finished nanocrystalline magnetic cores after cooling. The nanocrystalline magnetic cores obtained by the above method can be used in a leakage protector to protect against both AC leakage and DC pulsating current. However, both annealing processes in this method are single-stage heat preservation, which is not conducive to the elimination of internal stress and the stable transformation of the organization, resulting in unstable batch performance, thereby reducing the reliability when used as a residual current transformer core, and is not suitable for industrial mass production.
[0006] Therefore, it is necessary to provide a nanocrystalline soft magnetic alloy with low remanence and suitable initial magnetic permeability, and a preparation method and application thereof. Summary of the invention
[0007] The purpose of the present invention is to provide a nanocrystalline soft magnetic alloy and a preparation method and application thereof, and in particular to provide a nanocrystalline soft magnetic alloy suitable for type A residual current transformer and a preparation method and application thereof. The nanocrystalline soft magnetic alloy provided by the present invention can have both good magnetic properties and mechanical properties, can also avoid the adverse effects of excessive element doping on the performance of the nanocrystalline soft magnetic alloy, and has excellent AC and DC performance.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In the first aspect, the present invention provides a nanocrystalline soft magnetic alloy, which includes, in atomic percentage, 11.5-12.5at% Si, 8-9at% B, 1-1.5at% Cu, 1.8-2.5at% Nb, 0.01-0.05at% Ce, 0.4-0.6at% P, 0.48-0.52at% Zr and Co, 73.33-76.81at% Fe and the remainder of inevitable impurities.
[0010] The nanocrystalline soft magnetic alloy provided by the present invention adjusts the constituent elements so that the final product has both good magnetic properties and mechanical properties, and can also avoid the adverse effects of excessive element doping on the properties of the nanocrystalline soft magnetic alloy, so that the final nanocrystalline soft magnetic alloy has excellent AC and DC properties.
[0011] The specific elements included in the nanocrystalline soft magnetic alloy provided by the present invention include Si, B, Cu, Nb, Ce, P, Zr, Co, Fe and inevitable impurities. The present invention improves the forming ability of the amorphous system, controls the grain size and reduces the iron loss by adding the Zr element; the present invention improves the Curie point by adding the Co element, so that the final nanocrystalline soft magnetic alloy has higher toughness; the present invention promotes the uniform distribution of the nanophase, improves the nucleation rate and inhibits the unstable growth of the grains by adding the Ce element and combining Ce with residual oxygen; the present invention controls the grain size and reduces the coercive force by adding the P element.
[0012] In addition, in the nanocrystalline soft magnetic alloy provided by the present invention, Cu serves as the crystallization core of α-Fe in the nanocrystallization process and is the catalyst of the entire nanocrystalline soft magnetic alloy system. The combination of Cu-P can promote the dispersion and precipitation of Cu, while Zr, Ce, and Si also promote the combination of Cu-P and alleviate the precipitation of Fe-B phase.
[0013] It is necessary to avoid excessive or insufficient doping elements in the nanocrystalline soft magnetic alloy provided by the present invention, so as to avoid the adverse effects of the doping elements on the performance of the nanocrystalline soft magnetic alloy.
[0014] Specifically, when the Si element content is too much, the brittleness of the nanocrystalline soft magnetic alloy will increase and the saturation magnetic induction intensity will be reduced, which is not conducive to mass production; when the Si element content is too little, the high-temperature magnetic properties of the nanocrystalline soft magnetic alloy will be reduced, damaging its service life in extreme environments; therefore, in terms of atomic percentage, the nanocrystalline soft magnetic alloy includes 11.5-12.5at% Si, for example, it can be 11.5at%, 11.8at%, 12at%, 12.2at% or 12.5at%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] When the B element content is too much, the crystallization interval of the nanocrystalline soft magnetic alloy will decrease during the preparation process, reducing the α-Fe phase amount, resulting in increased remanence, and there is a risk of affecting the accuracy of the residual current transformer; when the B element content is too little, the amorphous forming ability will be reduced; therefore, in terms of atomic percentage, the nanocrystalline soft magnetic alloy includes 8-9at% B, for example, it can be 8at%, 8.2at%, 8.5at%, 8.6at%, 8.8at% or 9at%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] When the Cu element content is too much, it will change the crystallization behavior during the preparation of the nanocrystalline soft magnetic alloy and affect the smooth formation of nanocrystals; when the Cu element content is too little, it will cause the grains in the resulting nanocrystalline soft magnetic alloy to be abnormally coarse; therefore, in terms of atomic percentage, the nanocrystalline soft magnetic alloy includes 1-1.5at% Cu, for example, it can be 1at%, 1.1at%, 1.2at%, 1.3at%, 1.4at% or 1.5at%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0017] When the Nb element content is too much, the cost of the nanocrystalline soft magnetic alloy will increase, resulting in excess performance; when the Nb element content is too little, the grains in the resulting nanocrystalline soft magnetic alloy will be abnormally coarse; therefore, in terms of atomic percentage, the nanocrystalline soft magnetic alloy includes 1.8-2.5at% Nb, for example, it can be 1.8at%, 2at%, 2.1at%, 2.4at% or 2.5at%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] When the Zr content is too much, the coexistence of excessive Zr and Cu will lead to a decrease in saturation magnetization, and more stringent atmosphere protection is required in the industrial preparation process; when the Zr content is too little, it cannot play a role in improving the ability to form an amorphous system, and it cannot effectively control the grain size; when the Co content is too much, the cost of the nanocrystalline soft magnetic alloy will increase, causing a significant increase in the cost of the nanocrystalline soft magnetic alloy, and will lead to a decrease in the room temperature saturation magnetic induction intensity; when the Co content is too little, it cannot effectively improve the toughness of the resulting nanocrystalline soft magnetic alloy. Therefore, in terms of atomic percentage, the nanocrystalline soft magnetic alloy includes 0.48-0.52at% of Zr and Co, for example, it can be 0.48at%, 0.49at%, 0.5at%, 0.51at% or 0.52at%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0019] When the Ce element content is too much, Ce will affect the smooth formation of the nanocrystalline structure, and the slag generated during the preparation process will affect the smelting effect; when the Ce element content is too little, it cannot effectively promote the uniform distribution of the nanophase and cannot effectively inhibit the unstable growth of the grains; therefore, in terms of atomic percentage, the nanocrystalline soft magnetic alloy includes 0.01-0.05at% Ce, for example, it can be 0.01at%, 0.02at%, 0.03at%, 0.04at% or 0.05at%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] When the P element content is too much, the saturation magnetic induction of the final nanocrystalline soft magnetic alloy will decrease, and the solution will oxidize during the preparation process; when the P element content is too little, the coercive force cannot be effectively reduced; therefore, in terms of atomic percentage, the nanocrystalline soft magnetic alloy includes 0.4-0.6at% P, for example, it can be 0.4at%, 0.45at%, 0.5at%, 0.55at% or 0.6at%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] In terms of atomic percentage, the nanocrystalline soft magnetic alloy includes 73.33-76.81at% Fe, for example, it can be 73.33at%, 73.72at%, 74.22at%, 74.77at%, 74.95at%, 75.22at%, 75.37at%, 75.67at%, 76.22at%, 76.72at% or 76.81at%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] Preferably, in terms of atomic percentage, the Zr content in the nanocrystalline soft magnetic alloy is 0.2-0.3at%, for example, it can be 0.2at%, 0.22at%, 0.25at%, 0.28at% or 0.3at%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] Correspondingly, in terms of atomic percentage, the Co content in the nanocrystalline soft magnetic alloy is 0.2-0.3at%, for example, it can be 0.2at%, 0.22at%, 0.25at%, 0.28at% or 0.3at%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] In a second aspect, the present invention provides a method for preparing the nanocrystalline soft magnetic alloy as described in the first aspect, the preparation method comprising the following steps:
[0025] An amorphous strip having a formula element composition is wound into a magnetic ring, and then the magnetic ring is subjected to a first heat treatment to obtain a heat-treated magnetic ring; the heat-treated magnetic ring is subjected to a second heat treatment under conditions below the crystallization temperature, and a transverse magnetic field is applied during the second heat treatment to obtain the nanocrystalline soft magnetic alloy.
[0026] The preparation method provided by the present invention performs a second heat treatment at a temperature lower than the crystallization temperature after the first heat treatment, so that the material is heated evenly, the orderly change of the magnetic domain inside the material is controlled, and the material obtains excellent AC and DC performance. Compared with the one-step magnetic field heat treatment method in the prior art, the preparation method provided by the present invention can control the material structure to undergo a stable phase change. During the entire nanocrystallization and magnetization process, Si and B elements are combined with the first heat treatment and the second heat treatment to stably form the nanocrystals, reducing or avoiding the formation of Fe-B compounds; P and Zr can significantly refine the grain size during the second heat treatment; Co improves the high-temperature magnetic properties by forming Fe-Co alloys; Ce elements can have a significant metamorphic effect on the brittle phase during the first heat treatment and the second heat treatment, significantly improving the mechanical properties, so that the final nanocrystalline soft magnetic alloy has both high performance and high stability.
[0027] Exemplarily, the method for preparing the amorphous strip having the formulated elemental composition includes: melting a master alloy having the formulated elemental composition, and obtaining the amorphous strip by a single-roller strip spinning method in an atmospheric environment.
[0028] Exemplarily, the lamination coefficient of the magnetic ring is ≥ 0.8, for example, it can be 0.8, 0.83, 0.85, 0.88, 0.9 or 0.95, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Exemplarily, before the heat treatment magnetic ring is subjected to the second heat treatment, the step of passing the heat treatment magnetic ring through a rod and vertically inserting the rod into a magnetic field furnace rack is also included.
[0030] Preferably, the first heat treatment includes: under a protective atmosphere, heating the magnetic ring to a first temperature for a first insulation, then heating it to a second temperature for a second insulation, and then heating it to a third temperature for a third insulation; after the third insulation is completed, cooling it to a fourth temperature with the furnace, and then filling it with a protective gas for cooling.
[0031] Preferably, the first temperature is lower than the second temperature;
[0032] The second temperature is lower than the third temperature;
[0033] The fourth temperature is greater than the first temperature and less than the second temperature.
[0034] Preferably, the first heat treatment satisfies at least one of conditions (a1) to (a7):
[0035] (a1) the first temperature is 380-390° C., for example, 380° C., 382° C., 385° C., 388° C. or 390° C., but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0036] (a2) the first insulation time is 55-65 min, for example, 55 min, 58 min, 60 min, 63 min or 65 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0037] (a3) the second temperature is 480-490° C., for example, 480° C., 483° C., 485° C., 488° C. or 490° C., but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0038] (a4) the second insulation time is 170-190 min, for example, 170 min, 175 min, 180 min, 185 min or 190 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0039] (a5) the third temperature is 560-570° C., for example, 560° C., 563° C., 565° C., 568° C. or 570° C., but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0040] (a6) the third insulation time is 55-65 min, for example, 55 min, 58 min, 60 min, 63 min or 65 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0041] (a7) The fourth temperature is 390-410°C, for example, 390°C, 395°C, 400°C, 405°C or 410°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0042] Preferably, the second heat treatment includes: under a protective atmosphere, heating the heat treatment magnetic ring to a fifth temperature for a fifth heat preservation, then heating it to a sixth temperature for a sixth heat preservation, and cooling it to room temperature after the sixth heat preservation; during the second heat treatment process, when the temperature reaches a peak value, applying a transverse magnetic field, and removing the transverse magnetic field when cooling to the seventh temperature.
[0043] For the convenience of expression, the "fourth heat preservation" is not set in the preparation method provided by the present invention, so as to facilitate the correspondence between the fifth heat preservation and the fifth temperature.
[0044] Preferably, the second heat treatment satisfies at least one of the conditions (b1) to (b):
[0045] (b1) the fifth temperature is 370-470° C., for example, 370° C., 380° C., 400° C., 420° C., 450° C. or 470° C., but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0046] (b2) the fifth insulation time is 55-65 min, for example, 55 min, 58 min, 60 min, 63 min or 65 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0047] (b3) the sixth temperature is 400-500° C., for example, 400° C., 420° C., 450° C., 480° C. or 500° C., but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0048] (b4) The sixth insulation time is 55-65 min, for example, 55 min, 58 min, 60 min, 63 min or 65 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0049] (b5) The seventh temperature is 180-220°C, for example, it can be 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C or 220°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In the present invention, if the fifth temperature is too high or too low, it will lead to uneven temperature field distribution, affecting the performance consistency of the entire furnace and even affecting the qualified rate.
[0051] In the present invention, if the sixth temperature is too high or too low, it will cause incomplete rotation or excessive rotation of the magnetic domains, which will also affect the consistency and qualified rate of the entire furnace.
[0052] The first heat treatment of the present invention is carried out in a protective atmosphere, and the protective gas used in the protective atmosphere includes any one of nitrogen, helium, neon or argon, or a combination of at least two of them. Typical but non-limiting combinations include a combination of nitrogen and helium, a combination of helium and neon, a combination of neon and argon, a combination of nitrogen, helium and neon, a combination of helium, neon and argon, or a combination of nitrogen, helium, neon and argon.
[0053] Exemplarily, forming a protective atmosphere for the first heat treatment includes the following steps: performing vacuuming and purging in sequence, and then introducing a protective gas to form a protective atmosphere.
[0054] The second heat treatment of the present invention is carried out in a protective atmosphere, and the protective gas used in the protective atmosphere includes any one of nitrogen, helium, neon or argon, or a combination of at least two of them. Typical but non-limiting combinations include a combination of nitrogen and helium, a combination of helium and neon, a combination of neon and argon, a combination of nitrogen, helium and neon, a combination of helium, neon and argon, or a combination of nitrogen, helium, neon and argon.
[0055] Exemplarily, forming the protective atmosphere for the second heat treatment includes the following steps: performing vacuuming and purging in sequence, and then introducing a protective gas to form the protective atmosphere.
[0056] Preferably, the strength of the transverse magnetic field is 700-900 Gs, for example, it may be 700 Gs, 720 Gs, 750 Gs, 780 Gs, 800 Gs, 820 Gs, 850 Gs, 880 Gs or 900 Gs, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In the present invention, if the intensity of the transverse magnetic field is too high, it is very easy to saturate in advance and cause waste of production resources; if the intensity of the transverse magnetic field is too low, it will lead to poor magnetic properties and too low cross-to-direct ratio.
[0058] In a third aspect, the present invention provides a type A residual current transformer, wherein the type A residual current transformer comprises the nanocrystalline soft magnetic alloy described in the first aspect.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] (1) The nanocrystalline soft magnetic alloy provided by the present invention adjusts the constituent elements so that the final product has both good magnetic properties and mechanical properties, and can also avoid the adverse effects of excessive element doping on the properties of the nanocrystalline soft magnetic alloy, so that the final nanocrystalline soft magnetic alloy has excellent AC and DC properties;
[0061] (2) Compared with the one-step magnetic field heat treatment method in the prior art, the preparation method provided by the present invention can control the material structure to undergo a stable phase change. During the entire nanocrystallization and magnetization process, Si and B elements are combined with the first heat treatment and the second heat treatment to stabilize the nanocrystals and reduce or avoid the formation of Fe-B compounds; P and Zr can significantly refine the grain size during the second heat treatment; Co improves the high-temperature magnetic properties by forming an Fe-Co alloy; Ce elements can have a significant metamorphic effect on the brittle phase during the first heat treatment and the second heat treatment, significantly improving the mechanical properties, so that the final nanocrystalline soft magnetic alloy has both high performance and high stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1It is a schematic diagram of the structure of the vacuum heat treatment tray used in the specific implementation manner.
[0063] Figure 2 It is a structural schematic diagram of a magnetic field furnace charge rack in a specific implementation manner.
[0064] Figure 3 It is a schematic diagram of a specific implementation method after the magnetic ring through rod is vertically inserted. DETAILED DESCRIPTION
[0065] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0066] In order to clearly illustrate the technical solution of the present invention, the magnetic ring in the specific embodiment is prepared by the following preparation method: melting the master alloy with the formula amount, and using the single-roller belt method to spin the molten master alloy in an atmospheric environment with a speed of more than 10 4 K / s cooling rate, a completely amorphous strip with a thickness of 30 μm and a width of 20 mm is obtained, and a winding machine is used to wind it into a magnetic ring with an inner diameter × outer diameter × height of 10 mm × 15 mm × 20 mm; the preparation method of the magnetic ring is only for the purpose of clearly illustrating the technical solution of the present invention and is not regarded as a further limitation of the magnetic ring.
[0067] In order to clearly illustrate the technical solution of the present invention, the structural schematic diagram of the vacuum heat treatment tray used in the first heat treatment in the specific embodiment is as follows: Figure 1 As shown, its material is high temperature resistant SUS304 stainless steel, and the disk body is provided with a close-packed 60° angle array of circular holes to ensure thermal field stability and uniform heating of the magnetic ring; the structural schematic diagram of the magnetic field furnace rack used in the second heat treatment in the specific implementation method is shown in Figure 2 As shown, the material is non-magnetic stainless steel, and a hole is reserved in the middle for the transverse magnetic generating mechanism to pass through; the schematic diagram of the magnetic ring through rod after vertical insertion is as shown Figure 3 As shown, the bottom of the magnetic field furnace rack is provided with ventilation holes to facilitate heating and cooling gas convection and reduce the heat capacity of the rack itself.
[0068] Example 1
[0069] The present embodiment provides a nanocrystalline soft magnetic alloy, which includes, in atomic percentage, 11.5at% Si, 8at% B, 1.5at% Cu, 2.5at% Nb, 0.01at% Ce, 0.6at% P, 0.32at% Zr, 0.2at% Co and 75.37at% Fe.
[0070] The preparation method of the nanocrystalline soft magnetic alloy comprises the following steps:
[0071] (1) The master alloy is melted, and the molten master alloy is subjected to a single-roller strip-spinning method to obtain an amorphous strip in an atmospheric environment, and then is wound into a magnetic ring with an inner diameter × outer diameter × height of 10 mm × 15 mm × 20 mm and a lamination factor of 0.83 using a winding machine;
[0072] In terms of atomic percentage, the master alloy includes 11.5 at% Si, 8 at% B, 1.5 at% Cu, 2.5 at% Nb, 0.01 at% Ce, 0.6 at% P, 0.32 at% Zr, 0.2 at% Co and 75.37 at% Fe;
[0073] (2) Place the magnetic ring flat and without squeezing it in a vacuum heat treatment plate, evacuate and wash it, and then introduce nitrogen as a protective gas; then heat the magnetic ring to 385°C and keep it for 60 minutes, then heat it to 485°C and keep it for 180 minutes, and then heat it to 565°C and keep it for 60 minutes; after the insulation is completed, cool it to 400°C with the furnace, fill it with nitrogen for cooling, and obtain a heat-treated magnetic ring;
[0074] (3) The obtained magnetic rings are passed through rods and vertically inserted into a magnetic field furnace rack without the magnetic rings touching each other. Vacuuming and purging are then performed, and nitrogen is introduced as a protective gas. The heat-treated magnetic rings are then heated to 470°C and kept warm for 60 min, and then heated to 500°C and kept warm for 60 min. After the insulation period, they are cooled to room temperature. During the second heat treatment process, when the temperature reaches the peak value, a transverse magnetic field of 700 Gs is applied. When the temperature is cooled to 200°C, the transverse magnetic field is removed to obtain a nanocrystalline soft magnetic alloy.
[0075] Example 2
[0076] The present embodiment provides a nanocrystalline soft magnetic alloy, which includes, in atomic percentage, 12.5at% Si, 9at% B, 1at% Cu, 1.8at% Nb, 0.05at% Ce, 0.4at% P, 0.2at% Zr, 0.28at% Co and 74.95at% Fe.
[0077] The preparation method of the nanocrystalline soft magnetic alloy comprises the following steps:
[0078] (1) The master alloy is melted, and the molten master alloy is subjected to a single-roller strip-spinning method to obtain an amorphous strip in an atmospheric environment, and then is wound into a magnetic ring with an inner diameter × outer diameter × height of 10 mm × 15 mm × 20 mm and a lamination factor of 0.83 using a winding machine;
[0079] In terms of atomic percentage, the master alloy includes 12.5 at% Si, 9 at% B, 1 at% Cu, 1.8 at% Nb, 0.05 at% Ce, 0.4 at% P, 0.2 at% Zr, 0.28 at% Co and 74.95 at% Fe;
[0080] (2) Place the magnetic ring flat and without squeezing it in a vacuum heat treatment plate, evacuate and purge it, and then introduce nitrogen as a protective gas; then heat the magnetic ring to 380°C and keep it for 65 minutes, then heat it to 480°C and keep it for 190 minutes, and then heat it to 560°C and keep it for 65 minutes; after the insulation is completed, cool it to 390°C with the furnace, fill it with nitrogen for cooling, and obtain a heat-treated magnetic ring;
[0081] (3) The obtained magnetic rings are passed through a rod and vertically inserted into a magnetic field furnace rack without the magnetic rings touching each other. Vacuuming and purging are then performed, and nitrogen is introduced as a protective gas. The heat-treated magnetic rings are then heated to 370°C and kept warm for 65 min, and then heated to 400°C and kept warm for 65 min. After the insulation period, they are cooled to room temperature. During the second heat treatment process, when the temperature reaches the peak value, a transverse magnetic field of 900 Gs is applied. When the temperature is cooled to 200°C, the transverse magnetic field is removed to obtain a nanocrystalline soft magnetic alloy.
[0082] Example 3
[0083] The present embodiment provides a nanocrystalline soft magnetic alloy, which includes, in atomic percentage, 12at% Si, 8.5at% B, 1.25at% Cu, 2at% Nb, 0.03at% Ce, 0.5at% P, 0.25at% Zr, 0.25at% Co and 75.22at% Fe.
[0084] The preparation method of the nanocrystalline soft magnetic alloy comprises the following steps:
[0085] (1) The master alloy is melted, and the molten master alloy is subjected to a single-roller strip-spinning method to obtain an amorphous strip in an atmospheric environment, and then is wound into a magnetic ring with an inner diameter × outer diameter × height of 10 mm × 15 mm × 20 mm and a lamination factor of 0.83 using a winding machine;
[0086] In terms of atomic percentage, the master alloy includes 12 at% Si, 8.5 at% B, 1.25 at% Cu, 2 at% Nb, 0.03 at% Ce, 0.5 at% P, 0.25 at% Zr, 0.25 at% Co and 75.22 at% Fe;
[0087] (2) Place the magnetic ring flat and without squeezing it in a vacuum heat treatment plate, evacuate and purge it, and then introduce nitrogen as a protective gas; then heat the magnetic ring to 390°C and keep it for 55 minutes, then heat it to 490°C and keep it for 170 minutes, and then heat it to 570°C and keep it for 55 minutes; after the insulation is completed, cool it to 410°C with the furnace, fill it with nitrogen for cooling, and obtain a heat-treated magnetic ring;
[0088] (3) The obtained magnetic rings are passed through rods and vertically inserted into a magnetic field furnace rack without the magnetic rings touching each other. Vacuuming and purging are then performed, and nitrogen is introduced as a protective gas. The heat-treated magnetic rings are then heated to 420°C and kept warm for 55 min, and then heated to 450°C and kept warm for 55 min. After the insulation period, they are cooled to room temperature. During the second heat treatment process, when the temperature reaches the peak value, a transverse magnetic field of 800 Gs is applied. When the temperature is cooled to 200°C, the transverse magnetic field is removed to obtain a nanocrystalline soft magnetic alloy.
[0089] Comparative Example 1
[0090] This comparative example provides a nanocrystalline soft magnetic alloy, which includes, in atomic percentage, 11.5at% Si, 8at% B, 1.5at% Cu, 2.5at% Nb, 0.01at% Ce, 0.6at% P, 0.32at% Zr, 0.2at% Co and 75.37at% Fe.
[0091] The preparation method of the nanocrystalline soft magnetic alloy comprises the following steps:
[0092] (1) The master alloy is melted, and the molten master alloy is subjected to a single-roller strip-spinning method to obtain an amorphous strip in an atmospheric environment, and then is wound into a magnetic ring with an inner diameter × outer diameter × height of 10 mm × 15 mm × 20 mm and a lamination factor of 0.83 using a winding machine;
[0093] In terms of atomic percentage, the master alloy includes 11.5 at% Si, 8 at% B, 1.5 at% Cu, 2.5 at% Nb, 0.01 at% Ce, 0.6 at% P, 0.32 at% Zr, 0.2 at% Co and 75.37 at% Fe;
[0094] (2) Place the magnetic ring flat and without squeezing it in a vacuum heat treatment plate, evacuate and wash it, and then introduce nitrogen as a protective gas; then heat the magnetic ring to 385°C and keep it for 60 minutes, then heat it to 485°C and keep it for 180 minutes, and then heat it to 565°C and keep it for 60 minutes; after the insulation is completed, cool it to 400°C with the furnace, fill it with nitrogen for cooling, and obtain a heat-treated magnetic ring;
[0095] During the first heat treatment, when the temperature reaches a peak value, a transverse magnetic field of 700 Gs is applied, and when the temperature is cooled to 200° C., the transverse magnetic field is removed to obtain a nanocrystalline soft magnetic alloy.
[0096] Comparative Example 2
[0097] This comparative example provides a nanocrystalline soft magnetic alloy, which includes, in atomic percentage, 12.5at% Si, 9at% B, 1at% Cu, 1.8at% Nb, 0.05at% Ce, 0.4at% P, 0.2at% Zr, 0.28at% Co and 74.95at% Fe.
[0098] The preparation method of the nanocrystalline soft magnetic alloy comprises the following steps:
[0099] (1) The master alloy is melted, and the molten master alloy is subjected to a single-roller strip-spinning method to obtain an amorphous strip in an atmospheric environment, and then is wound into a magnetic ring with an inner diameter × outer diameter × height of 10 mm × 15 mm × 20 mm and a lamination factor of 0.83 using a winding machine;
[0100] In terms of atomic percentage, the master alloy includes 12.5 at% Si, 9 at% B, 1 at% Cu, 1.8 at% Nb, 0.05 at% Ce, 0.4 at% P, 0.2 at% Zr, 0.28 at% Co and 74.95 at% Fe;
[0101] (2) Place the magnetic ring flat and without squeezing it in a vacuum heat treatment plate, evacuate and purge it, and then introduce nitrogen as a protective gas; then heat the magnetic ring to 380°C and keep it for 65 minutes, then heat it to 480°C and keep it for 190 minutes, and then heat it to 560°C and keep it for 65 minutes; after the insulation is completed, cool it to 390°C with the furnace, fill it with nitrogen for cooling, and obtain a heat-treated magnetic ring;
[0102] During the first heat treatment, when the temperature reaches a peak value, a transverse magnetic field of 900 Gs is applied, and when the temperature is cooled to 200° C., the transverse magnetic field is removed to obtain a nanocrystalline soft magnetic alloy.
[0103] Comparative Example 3
[0104] This comparative example provides a nanocrystalline soft magnetic alloy, which includes, in atomic percentage, 12at% Si, 8.5at% B, 1.25at% Cu, 2at% Nb, 0.03at% Ce, 0.5at% P, 0.25at% Zr, 0.25at% Co and 75.22at% Fe.
[0105] The preparation method of the nanocrystalline soft magnetic alloy comprises the following steps:
[0106] (1) The master alloy is melted, and the molten master alloy is subjected to a single-roller strip-spinning method to obtain an amorphous strip in an atmospheric environment, and then is wound into a magnetic ring with an inner diameter × outer diameter × height of 10 mm × 15 mm × 20 mm and a lamination factor of 0.83 using a winding machine;
[0107] In terms of atomic percentage, the master alloy includes 12 at% Si, 8.5 at% B, 1.25 at% Cu, 2 at% Nb, 0.03 at% Ce, 0.5 at% P, 0.25 at% Zr, 0.25 at% Co and 75.22 at% Fe;
[0108] (2) Place the magnetic ring flat and without squeezing it in a vacuum heat treatment plate, evacuate and purge it, and then introduce nitrogen as a protective gas; then heat the magnetic ring to 390°C and keep it for 55 minutes, then heat it to 490°C and keep it for 170 minutes, and then heat it to 570°C and keep it for 55 minutes; after the insulation is completed, cool it to 410°C with the furnace, fill it with nitrogen for cooling, and obtain a heat-treated magnetic ring;
[0109] During the first heat treatment, when the temperature reaches a peak value, a transverse magnetic field of 800 Gs is applied, and when the temperature is cooled to 200° C., the transverse magnetic field is removed to obtain a nanocrystalline soft magnetic alloy.
[0110] Comparative Example 4
[0111] This comparative example provides a nanocrystalline soft magnetic alloy, which includes, in atomic percentage, 12at% Si, 8.5at% B, 1.25at% Cu, 2at% Nb, 0.03at% Ce, 0.5at% P, 0.5at% Co and 75.22at% Fe.
[0112] The preparation method of the nanocrystalline soft magnetic alloy comprises the following steps:
[0113] (1) The master alloy is melted, and the molten master alloy is subjected to a single-roller strip-spinning method to obtain an amorphous strip in an atmospheric environment, and then is wound into a magnetic ring with an inner diameter × outer diameter × height of 10 mm × 15 mm × 20 mm and a lamination factor of 0.83 using a winding machine;
[0114] In terms of atomic percentage, the master alloy includes 12 at% Si, 8.5 at% B, 1.25 at% Cu, 2 at% Nb, 0.03 at% Ce, 0.5 at% P, 0.5 at% Co and 75.22 at% Fe;
[0115] (2) Place the magnetic ring flat and without squeezing it in a vacuum heat treatment plate, evacuate and purge it, and then introduce nitrogen as a protective gas; then heat the magnetic ring to 390°C and keep it for 55 minutes, then heat it to 490°C and keep it for 170 minutes, and then heat it to 570°C and keep it for 55 minutes; after the insulation is completed, cool it to 410°C with the furnace, fill it with nitrogen for cooling, and obtain a heat-treated magnetic ring;
[0116] During the first heat treatment, when the temperature reaches a peak value, a transverse magnetic field of 800 Gs is applied, and when the temperature is cooled to 200° C., the transverse magnetic field is removed to obtain a nanocrystalline soft magnetic alloy.
[0117] The nanocrystalline soft magnetic alloys provided in Comparative Examples 5 to 17 are the same as those in Example 3 except that the composition of the master alloy is shown in Table 1.
[0118] Table 1
[0119]
[0120] Performance Testing
[0121] The performance of the nanocrystalline soft magnetic alloys provided in Examples 1-3 and Comparative Examples 1-17 was tested, and the results are shown in Table 2, including:
[0122] (1) The remanence Br and initial magnetic permeability μ are measured using a soft magnetic DC test system. i Conduct testing;
[0123] (2) Using AC 50Hz, the primary input is 42mA turns, and a 0.21Ω resistor is connected in parallel. The output characteristic of the secondary side is 1 turn U1; pulsating DC positive direction, the primary input is 42mA turns, and a 0.21Ω resistor is connected in parallel. The output characteristic of the secondary side is 1 turn U1, and the AC-DC ratio is U2 / U1;
[0124] (3) Collect performance data of the entire furnace and calculate performance fluctuations of samples.
[0125] Table 2
[0126]
[0127]
[0128] It can be seen from Table 2 that the nanocrystalline soft magnetic alloy provided by the present invention has good magnetic properties, a high AC-DC ratio, and low performance fluctuation during the preparation process, and is particularly suitable for mass production and application of type A residual current transformers.
[0129] From the comparison between comparative example 1 and example 1, the comparison between comparative example 2 and example 2, and the comparison between comparative example 3 and example 3 of the present invention, it can be seen that when only the first heat treatment is performed, the magnetic properties of the obtained nanocrystalline soft magnetic alloy decrease, and it is impossible to have both good AC performance and pulsating DC performance.
[0130] From the comparison between Comparative Example 4 and Example 3 of the present invention, it can be seen that when the Zr element is not added to the composition of the nanocrystalline soft magnetic alloy, the performance of the obtained nanocrystalline soft magnetic alloy decreases, which is not conducive to its use in type A residual current transformer.
[0131] From the comparison between comparative example 5 of the present invention and embodiment 3, it can be seen that when the Co element is not added to the composition of the nanocrystalline soft magnetic alloy, the performance of the obtained nanocrystalline soft magnetic alloy decreases, and the performance fluctuation of the produced samples is large, which is not conducive to the production of type A residual current transformer.
[0132] From the comparison of comparative examples 6 and 7 of the present invention with embodiment 3, it can be seen that when the Si content in the nanocrystalline soft magnetic alloy composition is not within the process requirements, the performance of the obtained nanocrystalline soft magnetic alloy decreases, and the performance fluctuations of the produced samples are large, which is not conducive to the production of type A residual current transformers.
[0133] From the comparison of comparative examples 8 and 9 of the present invention with embodiment 3, it can be seen that when the B content in the composition of the nanocrystalline soft magnetic alloy is not within the process requirements, the performance of the obtained nanocrystalline soft magnetic alloy decreases, and the performance fluctuations of the produced samples are large, which is not conducive to the production of type A residual current transformers.
[0134] From the comparison of comparative examples 10 and 11 of the present invention with embodiment 3, it can be seen that when the Cu content in the nanocrystalline soft magnetic alloy composition is not within the process requirements, the performance of the obtained nanocrystalline soft magnetic alloy decreases, and the performance fluctuations of the produced samples are large, which is not conducive to the production of type A residual current transformers.
[0135] From the comparison of comparative examples 12 and 13 of the present invention with embodiment 3, it can be seen that when the Nb content in the nanocrystalline soft magnetic alloy composition is not within the process requirement range, the performance of the obtained nanocrystalline soft magnetic alloy decreases, which is not conducive to the production of type A residual current transformer.
[0136] From the comparison of comparative examples 14 and 15 of the present invention with embodiment 3, it can be seen that when the Ce content in the nanocrystalline soft magnetic alloy composition is not within the process requirements, the performance of the obtained nanocrystalline soft magnetic alloy decreases, and the performance fluctuations of the produced samples are large, which is not conducive to the production of type A residual current transformers.
[0137] From the comparison of comparative examples 16 and 17 of the present invention with embodiment 3, it can be seen that when the P content in the nanocrystalline soft magnetic alloy composition is not within the process requirement range, the performance of the obtained nanocrystalline soft magnetic alloy decreases, which is not conducive to the production of type A residual current transformer.
[0138] In summary, the nanocrystalline soft magnetic alloy provided by the present invention adjusts the constituent elements so that the final product has both good magnetic properties and mechanical properties, and can also avoid the adverse effects of excessive element doping on the performance of the nanocrystalline soft magnetic alloy, so that the final nanocrystalline soft magnetic alloy has excellent AC and DC properties; compared with the one-step magnetic field heat treatment method in the prior art, the preparation method provided by the present invention can control the material structure to undergo stable phase change. During the entire nanocrystallization and magnetization process, Si and B elements are combined with the first heat treatment and the second heat treatment to allow the nanocrystals to be stably formed, reducing or avoiding the formation of Fe-B compounds; P and Zr can significantly refine the grain size during the second heat treatment; Co improves the high-temperature magnetic properties by forming an Fe-Co alloy; the Ce element can have an obvious metamorphic effect on the brittle phase during the first heat treatment and the second heat treatment, significantly improving the mechanical properties, so that the final nanocrystalline soft magnetic alloy has both high performance and high stability.
[0139] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A nanocrystalline soft magnetic alloy, characterized in that: In terms of atomic percentage, the nanocrystalline soft magnetic alloy comprises 11.5-12.5 at% Si, 8-9 at% B, 1-1.5 at% Cu, 1.8-2.5 at% Nb, 0.01-0.05 at% Ce, 0.4-0.6 at% P, 0.48-0.52 at% Zr and Co, 73.33-76.81 at% Fe, and the balance is inevitable impurities; The content of Zr in the nanocrystalline soft magnetic alloy is 0.2-0.3at%; The nanocrystalline soft magnetic alloy is prepared by the following method, which comprises the following steps: The amorphous strip having the formula element composition is wound into a magnetic ring, and then the magnetic ring is subjected to a first heat treatment to obtain a heat-treated magnetic ring; the heat-treated magnetic ring is subjected to a second heat treatment under a condition lower than the crystallization temperature, and a transverse magnetic field is applied during the second heat treatment to obtain the nanocrystalline soft magnetic alloy; The first heat treatment comprises: in a protective atmosphere, heating the magnetic ring to a first temperature for a first heat preservation, then heating it to a second temperature for a second heat preservation, and then heating it to a third temperature for a third heat preservation; after the third heat preservation is completed, cooling it to a fourth temperature with the furnace, and then filling it with a protective gas for cooling; The first temperature is 380-390°C; the first insulation time is 55-65 minutes; the second temperature is 480-490°C; the second insulation time is 170-190 minutes; the third temperature is 560-570°C; the third insulation time is 55-65 minutes; the fourth temperature is 390-410°C; The second heat treatment comprises: in a protective atmosphere, heating the heat treatment magnetic ring to a fifth temperature for a fifth heat preservation, then heating it to a sixth temperature for a sixth heat preservation, and cooling it to room temperature after the sixth heat preservation; during the second heat treatment, when the temperature reaches a peak value, applying a transverse magnetic field, and removing the transverse magnetic field when cooling to the seventh temperature; The fifth temperature is 370-470°C; the fifth insulation time is 55-65min; the sixth temperature is 400-500°C; the sixth insulation time is 55-65min; the seventh temperature is 180-220°C.
2. A method for preparing the nanocrystalline soft magnetic alloy as claimed in claim 1, characterized in that: The preparation method comprises the following steps: The amorphous strip having the formula element composition is wound into a magnetic ring, and then the magnetic ring is subjected to a first heat treatment to obtain a heat-treated magnetic ring; the heat-treated magnetic ring is subjected to a second heat treatment under a condition lower than the crystallization temperature, and a transverse magnetic field is applied during the second heat treatment to obtain the nanocrystalline soft magnetic alloy; The first heat treatment comprises: in a protective atmosphere, heating the magnetic ring to a first temperature for a first heat preservation, then heating it to a second temperature for a second heat preservation, and then heating it to a third temperature for a third heat preservation; after the third heat preservation is completed, cooling it to a fourth temperature with the furnace, and then filling it with a protective gas for cooling; The first temperature is 380-390°C; the first insulation time is 55-65 minutes; the second temperature is 480-490°C; the second insulation time is 170-190 minutes; the third temperature is 560-570°C; the third insulation time is 55-65 minutes; the fourth temperature is 390-410°C; The second heat treatment comprises: in a protective atmosphere, heating the heat treatment magnetic ring to a fifth temperature for a fifth heat preservation, then heating it to a sixth temperature for a sixth heat preservation, and cooling it to room temperature after the sixth heat preservation; during the second heat treatment, when the temperature reaches a peak value, applying a transverse magnetic field, and removing the transverse magnetic field when cooling to the seventh temperature; The fifth temperature is 370-470°C; the fifth insulation time is 55-65min; the sixth temperature is 400-500°C; the sixth insulation time is 55-65min; the seventh temperature is 180-220°C.
3. The preparation method according to claim 2, characterized in that: The intensity of the transverse magnetic field is 700-900 Gs.
4. A type A residual current transformer, characterized in that: The A-type residual current transformer comprises the nanocrystalline soft magnetic alloy according to claim 1.
